Milton and Homer: "written to aftertimes" - Machacek, Gregory (Medieval & Renaissance literary studies, 2011)
"By allusion called" : diachronic and synchronic intertextuality -- "Dire example" : the war in Heaven as admonitory exemplum -- "A fabric wonderful" : the marvelous and verisimilar in Milton's Christian epic -- "From the first" : conceptions of origins and their consequences -- "Above th'Aonian mount" : the Longinian sublime in Paradise lost -- "Instruct me" : institutional considerations in Milton's evolving literary ambitions